Immunobiology of Pediatric Tuberculosis: Lessons Learned and Implications for an Improved TB-Vaccine - Boer, Mardi C.; Lewinsohn, Deborah A.; Lancioni, Christina L. (Journal of Pediatric Infectious Diseases, 2018)
Children, especially neonates and young infants, are uniquely vulnerable to tuberculosis (TB) and frequently present with primary progressive pulmonary or disseminated disease. There is an urgent need to understand the unique immunobiology of Mycobacterium tuberculosis (Mtb) in young infants and to identify protective infant immune responses. The existing vaccine against TB, Mycobacterium bovis bacillus Calmette–Guérin (M. bovis BCG), provides a partial protection against TB disease and disseminated forms of TB in infants; however, it is unknown how this partial protection is mediated. To end pediatric TB morbidity and mortality, a fully efficacious next-generation TB-vaccine is needed. Here, we focus on our current understanding of TB immunobiology as it pertains to young infants, and we evaluate what BCG-vaccination, as well as recently trialed novel TB-vaccines, has taught us about the immunobiology of mycobacterial infection in this population.
Keywords: tuberculosis; BCG; vaccine; Mtb; infant; pediatric; T cell; Immunity; immune response